Analysis of Chromosomal Copy Number in First-Trimester Pregnancy Loss Using Next-Generation Sequencing - Fan, Lei; Wu, Jianli; Wu, Yuanyuan; Shi, Xinwei; Xin, Xing; Li, Shufang; Zeng, Wanjiang; Deng, Dongrui; Feng, Ling; Chen, Suhua; Xiao, Juan (Frontiers in Genetics, 2020)
Embryonic chromosomal abnormality is one of the significant causative factors of early pregnancy loss. Our goal was to evaluate the clinical utility of next-generation sequencing (NGS) technology in identifying chromosomal anomalies associated with first-trimester pregnancy loss. In addition, we attempted to provide fertility guidance to couples anticipating a successful pregnancy. 1010 miscarriage specimens were collected between March 2016 and January 2019 from women who suffered first-trimester pregnancy loss. Total DNA was isolated from products of conception and NGS analysis was carried out. We detected a total of 634 cases of chromosomal variants. Among the 634 cases, 462(72.9%) displayed numerical variants including 383 (60.4%) aneuploidies, 44 (6.9%) polyploidies and 34 (5.5%) mosaicisms.The other 172(27.1%) cases showed structural variants including 19(3.0%) benign copy number variations (CNVs),52(8.2%) pathogenic CNVs and 101(16%) variants of unknown significance (VOUS) CNVs. When maternal age was ≥35 years, the spontaneous abortion(SA) group showed an increased frequency of chromosomal variants in comparison with the recurrent miscarriage(RM) group(90/121 vs. 64/104).It was evident that the groups with advanced maternal age had a sharply increased frequency of aneuploidy,whatever the frequency of pregnancy loss (71/121 vs.155/432, 49/104 vs. 108/349). Our data suggest that NGS could be used for the successful detection of genetic anomalies in pregnancy loss. We recommend that fetal chromosome analysis be offered routinely for all pregnancy losses, regardless of their frequency.